Effect of mould speed on selected properties of moulded parts and energy consumption in rotational moulding - Karolina Głogowska; Filip Longwic; Krzysztof Ludziak (Bulletin of the Polish Academy of Sciences: Technical Sciences, 2022)
This paper deals with rotational moulding. The relationship between mould speed and wall thickness in the upper, middle and lower areas of rotational moulded parts is investigated. Young’s modulus of moulded parts is determined via static tensile testing. A static compression test is performed to determine the maximum compressive force causing strain. The test is conducted on the wall of moulded parts, parallel to the main axis of rotation. Also, energy consumption in rotational moulding is investigated for different rotational speeds of the mould. Moulded parts are made of DOWLEX®2629UE linear low-density polyethylene (LLDPE). Experimental results are statistically analysed using STATISTICA 13. Non-parametric statistical tests are used for results analysis. The ANOVA method is employed to determine if there are any significant differences between obtained results. The statistical tests show that the range is much narrower for a speed ratio of 4:1. The narrowest range value is obtained for 12 3 rpm. The highest Young’s modulus values are obtained for the parts moulded at 12 3 rpm (1263.33 MPa) and 16 4 rpm (1263.67 MPa). The highest maximum compressive force is obtained for the parts moulded at 12 3 rpm (10 400 N). An analysis of the results demonstrates that the part moulded at 12 3 rpm has the most advantageous properties. For this mould speed, the power consumption amounts to 8.28 kWh. Experimental results and statistical analyses demonstrate that mould speed affects both moulded part quality and energy consumption in the rotational moulding process.